Delaying supplier payments to increase buyer profits. Issue 1 (31st October 2022) - Kovach, Jeremy J.; Swink, Morgan; Rodriguez, Mauricio
Abstract: As a means of acquiring trade credit, delaying supplier payments by extending payables (days to payment) offer financial benefits for buyers. However, such extensions may also engender costly supplier retaliation that results in operational disruptions and financial loss. Terms of payment between buyers and suppliers often affect the relationships established between trade partners; thus, changes to these terms should be evaluated within a social context. Social exchange theory (SET) is applied to analyze the benefits and costs of abrupt payable extensions on buyers' operational outcomes and profitability. The findings indicate that buyers who delay supplier payables by abruptly lengthening payables tend to subsequently increase investments in accounts receivable, inventory, and capital expenditures. Contrary to popular expectations, however, these buyers financially underperform when compared with similar (matched) firms that do not raise payables. Further analysis indicates that these buyers also experience greater supplier turnover and increases in indirect costs. These results are consistent with the expectation of retaliatory supplier responses to payable extensions. It is also revealed that the detrimental effects of delaying supplier payments by payable extensions are significantly smaller for more powerful and financially stronger firms. However, the relationships between payable extensions and capital‐based benefits do not appear to be contingent on buyer power or financial strength. This study extends SET by applying it as a lens through which researchers can examine shifts in trade credit terms. The findings suggest a broadened scope of factors to be considered in social exchange and offer new operationalizations of power and trust factors often addressed in SET studies. The study ends with a discussion of the implications of these findings for practice and future research.